Trend in mortality from mental and behavioral disorders due to alcohol use in Brazil, 2010-2021 - Wygor Bruno e Silva Morais; Fernando Ferraz do Nascimento; Jardeliny Corrêa da Penha; Jesusmar Ximenes Andrade; Márcio Dênis Medeiros Mascarenhas; Malvina Thais Pacheco Rodrigues (Ministério da Saúde do Brasil, 2024)
Abstract Objective: To analyze the trend in mortality from mental and behavioral disorders due to alcohol use in Brazil, 2010-2021. Methods: This was an time series study using Mortality Information System data. Annual percentage change (APC) and 95% confidence intervals (95% CI) were calculated using Prais-Winsten linear regression. Results: Mortality showed a stationary trend for Brazil as a whole (APC = 0.6; 95%CI -4.2;3.0), a falling trend in individuals aged 20-29 years in the South (APC = -7.4; 95%CI -10.0;-4.3) and Northeast (APC = -3.4; 95%CI -6.4;-0.4) regions, in people aged 30-39 in the Midwest region (APC = -3,8; 95%CI -7.4;-0.1) and 40-49 in the South (APC = -2.1; 95%CI -3.8;-0.4), North (APC = -3.1; 95%CI -5.7;-0.5) and Midwest (APC = -2.9; 95%CI -5.5;-0.3) regions. Conclusion: Mortality from mental and behavioral disorders due to alcohol use showed a stationary trend nationally and a falling trend in some age groups regionally.